Peran Remunerasi, Kompensasi, Kenyamanan Lingkungan Kerja, Beban Kerja, Pengembangan Karir dan Gaya Kepemimpinan Kepala Ruangan Terhadap Keinginan Pindah Kerja (Turnover) Perawat pada Masa Pandemi Covid-19: (Studi pada Rumah Sakit Sekarwangi Kabupaten Sukabumi) - Amir Hamzah (PT. Alahyan Publisher Sukabumi, 2024)
Coronavirus disease 2019 is a new type of coronavirus that not only affects the body, it can also seriously affect the mental health of residents. The phenomenon that mostly occurs when the performance of a hospital is said to be good at any time can be disrupted directly or indirectly by the attitude of nurses working in hospitals. The form of the nurse's attitude is the desire to change jobs (turnover) caused by several things, such as remuneration, compensation that is not appropriate, the absence of a comfortable work environment, high workload, lack of career development for nurses, and the leadership style of the head of the room. not good value. The purpose of this study was to analyze the relationship between the role of remuneration, compensation, comfort in the work environment, workload, career development and leadership style of the head of the room on the desire to change jobs (turnover) nurses. The sample used was 100 nurses. This study used an observational analytic method with a cross-sectional design. Data was collected through interviews, surveys, and distributing questionnaires. The data analysis technique used was logistic regression (logistic regression). The results of this study found that remuneration, compensation, workload, comfort in the work environment, and leadership style had a significant relationship to the desire to change jobs (turnover) of nurses during the Covid-19 pandemic at Sekarwangi Hospital, Sukabumi Regency.